Identification of a Novel Missense Mutation of POLR3A Gene in a Cohort of Sicilian Patients with Leukodystrophy - Antonino Musumeci; Francesco Calì; Carmela Scuderi; Mirella Vinci; Girolamo Aurelio Vitello; Sebastiano Antonino Musumeci; Valeria Chiavetta; Concetta Federico; Greta Amore; Salvatore Saccone; Gabriella Di Rosa; Antonio Gennaro Nicotera (Biomedicines, 2022)
Recessive mutations in the POLR3A gene cause POLR3-HLD (the second-most-common form of childhood-onset hypomyelinating leukodystrophy), a neurodegenerative disorder featuring deficient cerebral myelin formation. To date, more than 140 POLR3A (NM_007055.3) missense mutations are related to the pathogenesis of POLR3-related leukodystrophy and spastic ataxia. Herein, in a cohort of five families from Sicily (Italy), we detected two cases of patients affected by POLR3-related leukodystrophy, one due to a compound heterozygous mutation in the POLR3A gene, including a previously undescribed missense mutation (c.328A > G (p.Lys110Glu)). Our study used an in-house NGS gene panel comprising 41 known leukodystrophy genes. Successively, we used a predictive test supporting the missense mutation as causative of disease, thus this mutation can be considered “Likely Pathogenic” and could be as a new pathogenetic mutation of the POLR3A gene causing a severe form of POLR3-HLD.